Improving The Clean and Healthy Living Behavior of Adolescents in Rural Areas of Indonesia: An Educational Intervention Program - Novita Putri Eka Wardani; Nurul Kamila; Nadya Vallentina Febrianti; Rismawan Adi Yunanto (KHD Production, 2023)
Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat / PHBS) in schools is an effort to create a healthy environment in schools that is aware of preventing disease, improving health, and being active in maintaining a healthy environment in schools independently. This service aims to increase the awareness, attitudes, and PHBS skills of Tempurejo youth by counseling on clean and healthy living behavior based on the SI-TeSa mobile application. The quasi-experiment used pre-post and post-test questionnaires with research indicators, namely knowledge and attitudes, by dividing respondents into a control group (n=30) and an intervention group (n=30). Simple random sampling with a total of 60 respondents based on G power analysis (effect size 0.3, α err probability 0.05, power 0.95). Educational intervention program with PHBS education as well as two demonstrations including the 6 steps for washing hands and reviewing the SI-TeSa (Sistem Informasi Terampil Kesehatan) mobile application. The results of the pre-post Wilcoxon test for the intervention group showed a sig value <0.001 (p = 0.05). This indicates that there is an influence of education on clean and healthy living behavior based on the SI-TeSa mobile application. Meanwhile, the control group showed a sig value of 0.124 (p=0.05), indicating that there was no influence of education on clean and healthy living behavior. There was a significant increase in knowledge and attitude scores before and after the SI-TeSa mobile application-based healthy living behavior counseling was carried out.